Primary breast chondrosarcoma: Imaging and pathological findings - Amadu, Antonio Matteo (Eur J Radiol Open, 2017)
We present the case of a 62 year-old woman who was admitted to our institute of radiological sciences for a breast mass developed in the last few months. The final diagnosis was primary breast chondrosarcoma and the surgical treatment performed, based on imaging and pathological findings, was the mastectomy.